(untitled) (SAARC Journal of Agriculture, 2023)
Four genotypes of quail Dhakai (D), White (W), Brown (Br) and Black (Bl) quail are being maintained at BLRI with the objectives of increasing the sixth-week body weight through selective breeding and selecting parental birds and breeding them in an assortative plan for the production of 8th generation birds. The parent males and females were maintained in cages for single-pair mating through selective breeding system for producing each generation. A total of 1118-day-old quail chicks comprising 4 types were hatched in one batch to produce eighth generation (G8). The expected genetic progress due to selection for 5th-week body weight was estimated for G8. The genotype had significant (p<0.001) effect on the body weight of quails at 5th week of age. The 5th-week body weight was 132.34±0.88, 123.91±0.52, 104.29±0.76 and 105.36±0.68g, respectively for D, W, Br, and Bl genotypes. The hatchability rate was significantly (p<0.001) higher in D (78.47%) compared to other three genotypes. The egg production percentage up to 24th week of age was 85.27±1.0, 80.22±1.61, 81.07±1.2 and 96.12±1.1, respectively for D, W, Br, and Bl and significantly (p<0.001) differed among all genotypes. Mortality percent among genotypes was statistically non-significant (p>0.05). Sixth-week body weight of males of D, W, Br, and Bl quails were expected to increase by 4.06, 6.36, 2.39, and 3.12g, respectively. While in females of D, W, Br, and Bl quails, the responses were 5.60, 3.61, 4.17, and 3.91g, respectively. Taken together, it may be concluded that Dhakai quail was superior for body weight and Black quail for egg production performance. These findings suggested continuing the quail breeding research for producing a suitable meat-type quail genotype in our country. SAARC J. Agric., 21(1): 265-271 (2023)